2023
DOI: 10.1002/smll.202207877
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Cr‐Based Two‐Dimensional Conjugated Metal‐Organic Framework Through On‐Surface Substitution Reaction

Abstract: A single‐layer Cr3(HITP)2 (HITP = 2,3,6,7,10,11‐hexaiminotriphenylene) conjugated metal‐organic framework (c‐MOF) is synthesized under ultrahigh vacuum conditions by substituting Cr for Ni in Ni3(HITP)2 template. As revealed by low‐temperature scanning tunneling microscopy and scanning tunneling spectroscopy, while codeposition of Cr atoms and 2,3,6,7,10,11‐hexaaminotriphenylene precursors produces irregular branches, crystalline Cr3(HITP)2 frameworks are obtained by depositing Cr atoms to the Ni3(HITP)2 templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We found that the Type-I bands can be realized in monolayer Ni 3 (HITP) 2 grown on Au(111) substrate. Through the reported on-surface coordination assembly method 46 , 47 , monolayer Ni 3 (HITP) 2 frameworks are synthesized on Au(111) substrate from Ni atoms and 2,3,6,7,10,11-Hexaaminotriphenylene (HATP) molecules under ultrahigh vacuum conditions. The high quality of the synthesized Ni 3 (HITP) 2 frameworks are verified by STM image (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the Type-I bands can be realized in monolayer Ni 3 (HITP) 2 grown on Au(111) substrate. Through the reported on-surface coordination assembly method 46 , 47 , monolayer Ni 3 (HITP) 2 frameworks are synthesized on Au(111) substrate from Ni atoms and 2,3,6,7,10,11-Hexaaminotriphenylene (HATP) molecules under ultrahigh vacuum conditions. The high quality of the synthesized Ni 3 (HITP) 2 frameworks are verified by STM image (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is very inspirational that more than 10 000 products are being synthesized every year by employing various solid catalysts, which further trigger ≈15% of the world's GDP worth around $10 trillion per year. [ 1 ] In the contest of heterogeneous catalysis, Metal–organic frameworks (MOFs) have attracted immense attention over other solid catalysts having their unique structural features such as well‐defined pore structure and high porosity, [ 2–11 ] versatile functionality, [ 12–29 ] diverse composition, [ 30–46 ] tunable topography, [ 47–53 ] framework flexibility, [ 54–59 ] and improved stability. [ 60–62 ] Taking advantage of three different parts in MOFs, i) metal nodes, ii) employed organic ligands, and iii) the pore system , they have been explored in several multicomponent heterogeneous catalysis reactions such as condensations, oxidations, and C─C couplings, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, this option has been rarely studied within the field of metallosupramolecular surface networks, with the exception of a nitrogen−metal linked 2D conjugated system. 38 In particular, successful postsynthetic transformation of surface-confined 2D-OMNs with carbon−metal bonding, bearing significant prospects for appealing 2D graphyne-or graphdiyne-like materials with interesting electronic properties has not been reported so far.…”
mentioning
confidence: 99%
“…In-vacuum surface-adsorbed macrocycles, e.g., metalloporphyrins, have been reported to undergo transmetalation, facilitating the creation of macrocycles and the tuning of their properties for heterogeneous catalysis. Accordingly, in the context of surface-supported 2D OMNs, transmetalation appears as an appealing route for customizing the structure–property relationship of such attractive 2D materials in a controlled way. Surprisingly, this option has been rarely studied within the field of metallosupramolecular surface networks, with the exception of a nitrogen–metal linked 2D conjugated system . In particular, successful postsynthetic transformation of surface-confined 2D-OMNs with carbon–metal bonding, bearing significant prospects for appealing 2D graphyne- or graphdiyne-like materials with interesting electronic properties has not been reported so far.…”
mentioning
confidence: 99%